Pulmonary Function Abnormalities in Never Smoking Flight Attendants Exposed to Secondhand Tobacco Smoke in the Aircraft Cabin - Arjomandi, Mehrdad (2009)
OBJECTIVE: To determine whether the flight attendants who were exposed to secondhand tobacco smoke (SHS) in the aircraft cabin have abnormal pulmonary function. METHODS: We administered questionnaires and performed pulmonary function testing in 61 never-smoking female flight attendants who worked in active air crews before the smoking ban on commercial aircraft (pre-ban). RESULTS: While the pre-ban flight attendants had normal FVC, FEV(1), and FEV(1)/FVC ratio, they had significantly decreased flow at mid- and low-lung volumes, curvilinear flow-volume curves, and evidence of air trapping. Furthermore, the flight attendants had significantly decreased diffusing capacity (77.5±11.2 %predicted normal) with 51% having a diffusing capacity below their 95% normal prediction limit. CONCLUSIONS: This cohort of healthy never-smoking flight attendants who were exposed to SHS in the aircraft cabin showed pulmonary function abnormalities suggestive of airway obstruction and impaired diffusion.